Design of a Control System for an Automated Roselle Tea Process Plant. Issue 2 (December 2017) - Ayodeji, S.P.; Adeyeri, M.K.; Yakubu, A.M.; Ojo, O.O.
Abstract: Manual Sealing Process involves a lot of energy consumption with low productivity and the activities could be strenuous and non-hygienic. This work centred on the automation of such processes to achieving high production capacity and more hygienic products. Owing to high demand for Roselle Tea products as nourishment for healthy living, there is need to increase the production capacity by automating the production processes. In this research work, a control system was designed to automate a developed micro scale form- fill sealing machine which comprises electric motor for the rollers, crank mechanism for the sealing unit, Conveyor and Robotic arm. Control circuit was developed using Proteus Design software with a compiled code on PIC16F887 micro controller. This controller was programmed with a throughput of 25 packs per minute.